A Novel and Hybrid Post Quantum Cryptographic algorithm for Enhanced Security in Wireless Networks - Mutya Sirisha Adapa; Dr.P.Venkateswara Rao (Utilitas Mathematica, 2025)
Cryptography enables modern-day secure communication. The advancement of quantum algorithms has made classical cryptosystems ineffective. Important data has been encrypted and verified using digital signatures and cryptography. Classical cryptography systems were on the edge of collapse when quantum algorithms were introduced, since quantum computers can solve complex problems in less time. It is important to be prepared for future threats, even if standard cryptosystems are presumably safe for the moment being because quantum computing is not yet developed. One use of quantum cryptography is quantum key distribution (QKD), which is a way to safely share encryption keys between communication parties by utilizing quantum physics. Hybrid classical-quantum methods offer protection from both classical & quantum attackers, which can help smooth the way for the change. We introduce a new way to build hybrid encryption schemes from preexisting ones. First, the paper examines classical cryptosystems vulnerability to quantum computers. Then, it investigate into different families of post-quantum cryptosystems, checks in on the NIST's post-quantum cryptography consistency process, and finally, compares the performance of algorithms using post-quantum cryptography on various platforms. Along with discussing and evaluating current methods, this paper also discusses a novel hybrid quantum cryptographic system that employs message authentication codes with enhanced lattice based cryptography.